Diagnosis and Therapy of Psychosomatic Disorders in Reproductive Cycle of Women in General Medical Practice (Review) - V. E. Medvedev (SINAPS LLC, 2022)
The incidence of different psychiatric disorders (affective, anxious, dysmorphic, psychotic) during menstruation, pregnancy and the postpartum period reaches 80 %. Mental disorders are risk factors for the delayed onset and shortening of menstruations, manifestation of the premenstrual syndrome (PMS), inadequate emotional reactions during menstruations, disruptions in the menstrual cycle, decreased regularity and satisfaction of sexual activity, fertility, pregnancy failure, reduction of the lactation period, early onset of menopause with long duration and clinical severity of premenopause, etc. An individual approach to treatment should take into account risk factors (heredity, comorbid disorders, sex, age, etc.) of adverse events (AD), the balance of efficacy and safety of drugs